Portugal : Tenth Review Under the Extended Arrangement and Request for Waivers of Applicability of end-December Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Portugal's Tenth Review Under the Extended Arrangement and Request for Waivers of Applicability of End-December Performance Criteria (PCs). The short-term outlook for Portugal has improved and program implementation remains on track, notwithstanding another adverse Constitutional Court ruling. Stronger domestic demand is supporting a pickup in activity and lower unemployment. A broad-based recovery in sentiment has led to a decline in yields, allowing Portugal to issue a five-year bond on favorable terms. The end-September 2013 quantitative PCs were met, and preliminary estimates suggest that the end-December 2013 targets were also met. The IMF staff supports the authorities' request for completion of the 10th review and for waivers of applicability of the end-December PCs.